(untitled) (Transport systems and technologies, 2024)
The work is devoted to the study of the resonant frequency characteristics of the floor of passenger cars for the modernization of suburban electric trains of the EPL2, EPL9 series. A horizontal vibrator loading scheme was adopted for the experiments. The aim of the study is an experimental comparative assessment of the resonant frequencies of the floor of cars with different variants of the structural structure. An experimental and computational method for determining the resonant frequency of the oscillatory system based on limited experimental data, namely the excitation frequency and the measured coefficient of reduction of the force amplitude, is proposed. Based on the tests, the frequency characteristics of the relative change in the amplitude of accelerations on the surface of the floor of different structures were obtained. The relative amplitudes are presented in the form of the amplitude growth coefficient k. It is found that the floor amplitude growth coefficient does not depend on the excitation amplitude and depends only on the frequency. The frequency characteristics of the floor design options with rubber shock absorbers differ significantly from the basic version in terms of resonant frequency – 104 Hz versus 69–75 Hz. The introduction of layers of the vibration damping membrane into the design scheme has a minor effect on the resonant frequency of the floor: 75–71–69 Hz.